G protein-coupled receptor 35: an emerging target in inflammatory and cardiovascular disease - Divorty, Nina; Mackenzie, Amanda E.; Nicklin, Stuart A.; Milligan, Graeme (Frontiers in Pharmacology, 2015)
G protein coupled receptor 35 (GPR35) is an orphan receptor, discovered in 1998, that has garnered interest as a potential therapeutic target through its association with a range of diseases. However, a lack of pharmacological tools and the absence of convincingly defined endogenous ligands have hampered understanding of function necessary to exploit it therapeutically. Although several endogenous molecules can activate GPR35 none has yet been confirmed as the key endogenous ligand due to reasons that include lack of biological specificity, non-physiologically relevant potency and species ortholog selectivity. Recent advances have identified several highly potent synthetic agonists and antagonists, as well as agonists with equivalent potency at rodent and human orthologs, which will be useful as tool compounds. Homology modelling and mutagenesis studies have provided insight into the mode of ligand binding and possible reasons for the species selectivity of some ligands. Advances have also been made in determining the role of the receptor in disease. In the past, genome-wide association studies have associated GPR35 with diseases such as inflammatory bowel disease, type 2 diabetes and coronary artery disease. More recent functional studies have implicated it in processes as diverse as heart failure and hypoxia, inflammation, pain transduction and synaptic transmission. In this review, we summarise the progress made in understanding the molecular pharmacology, downstream signaling and physiological function of GPR35, and discuss its emerging potential applications as a therapeutic target.